Assessing vegetation phenology dynamics in West African rangelands: Implications for livestock sustainability and transhumance - Enrique Estefania-Salazar; Eva Iglesias (Ecological Informatics)
West African rangelands are essential for millions of people; however, they are considerably understudied. A substantial gap exists in regional investigations of livestock mobility and sustainability. Climate change, agricultural frontier expansion, and increasing herds intensify pressure on grazing lands. In this study, we aimed to assess the phenological parameters, such as the start, end, and length of the growing season, over more than 2.9 million km2 in 13 countries using 250-m resolution normalized difference vegetation index (NDVI) data for the 2003–2023 period. The NDVI dynamics within the growing season were studied through seasonal trend decomposition based on loess, focusing on seasonality, trends, and volatility. The results showed that the length of the growing season was diminishing primarily because of the delayed start of the season. This trend was more significant in the most productive southern areas and could have strong implications for traditional transhumance routes and sustainable carrying capacity. These findings are consistent with the existing literature and suggest that northern areas are greening whereas southern areas are browning. Finally, volatility is significantly increasing in areas with historically lower variability. This study underscores the necessity for climate adaptation strategies to mitigate the negative impacts of climate change on West African rangelands and ensure the sustainability of livestock production.